2016
DOI: 10.1139/cjfr-2015-0439
|View full text |Cite
|
Sign up to set email alerts
|

Prescribed burning of harvested boreal black spruce forests in eastern Canada: effect on understory vegetation

Abstract: Ecosystem-based management advocates that forestry disturbances should aim to emulate natural disturbances to mitigate the landscape-level impact of forest management. This study compares the impact of clear-cuts followed by a prescribed burn (CCPB) with clear-cuts alone (CC) and current careful logging practices (CLAAG: “careful logging around advanced growth”) on understory composition within black spruce (Picea mariana Miller (BSP)) paludified forest stands at the plot, site, and treatment levels using a fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 50 publications
1
1
0
Order By: Relevance
“…The lower abundance of larch regeneration in selective harvest plots was in agreement with the study which has reported reduced seed supply and lack of suitable microsites limites regenetation in these forested wetlands (Greene et al, 2007). Post-harvest understory communities are more similar to pre-harvest communities, with the exception of late successional shade intolerant species that do not survive stand opening caused by harvesting (Faivre et al, 2016). Additionally, large diameter trees of larch have not been burned to death, but most of birch trees died in the heavy fire, suggesting large larch is more fire-resistant than birch.…”
Section: Understory Species Diversitysupporting
confidence: 90%
“…The lower abundance of larch regeneration in selective harvest plots was in agreement with the study which has reported reduced seed supply and lack of suitable microsites limites regenetation in these forested wetlands (Greene et al, 2007). Post-harvest understory communities are more similar to pre-harvest communities, with the exception of late successional shade intolerant species that do not survive stand opening caused by harvesting (Faivre et al, 2016). Additionally, large diameter trees of larch have not been burned to death, but most of birch trees died in the heavy fire, suggesting large larch is more fire-resistant than birch.…”
Section: Understory Species Diversitysupporting
confidence: 90%
“…Managed forests should contain early-successional forests, which are critical for habitat specialists and disturbance-adapted species (Swanson et al 2011;Fedrowitz et al 2014). Prescribed burning after harvest has been suggested as a tool for promoting the unique substrates and habitats critical for fire-specialized species (McRae et al 2001;Hart and Chen 2006;Vanha-Majamaa et al 2007;Brassard and Chen 2010;Halpern et al 2012;Faivre et al 2016). When combined with aggregated tree retention, prescribed fire promoted the recovery of some plant species that have winddispersed seeds (Johnson et al 2014).…”
Section: Introductionmentioning
confidence: 99%